2005
DOI: 10.1016/j.bbmt.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation of HLA-Identical Sibling Culture-Expanded Mesenchymal Stem Cells and Hematopoietic Stem Cells in Hematologic Malignancy Patients

Abstract: Mesenchymal stem cells (MSCs) are found in a variety of tissues, including human bone marrow; secrete hematopoietic cytokines; support hematopoietic progenitors in vitro; and possess potent immunosuppressive properties. We hypothesized that cotransplantation of culture-expanded MSCs and hematopoietic stem cells (HSCs) from HLA-identical sibling donors after myeloablative therapy could facilitate engraftment and lessen graft-versus-host disease (GVHD); however, the safety and feasibility of this approach needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
516
1
15

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(548 citation statements)
references
References 55 publications
16
516
1
15
Order By: Relevance
“…Using cells isolated in this manner, we observed that MSC significantly reduced the mortality of GVHD as evidenced by survival data and supportive histological analyses. These data correlate to findings reported in clinical studies [22,24,47]. MSC had no significant efficacy when given at the time of transplant, on day 0, but significantly improved GVHD mortality when given during ongoing GVHD, on day 20.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using cells isolated in this manner, we observed that MSC significantly reduced the mortality of GVHD as evidenced by survival data and supportive histological analyses. These data correlate to findings reported in clinical studies [22,24,47]. MSC had no significant efficacy when given at the time of transplant, on day 0, but significantly improved GVHD mortality when given during ongoing GVHD, on day 20.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, when given at the time of BM transplant, for the prevention of GVHD, the incidence of grade III/ IV GVHD was not significantly improved [24], suggesting the absence of necessary initiating factors for MSC activation and subsequent efficient suppression of donor-derived T cells. MSC may require activating signals from robustly proliferating T cells to induce their suppressive effects.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, interest in MSCs has already moved from in vitro and animal studies into actual clinical trials in patients [36]. Several phase I-II clinical trials have already shown the safety and efficacy of BM-derived MSCs for enhancing the engraftment of co-transplanted HSCs in patients with hematologic and non-hematologic malignancies [37,38]. BM-derived MSCs have also shown promising results for the treatment of mesenchymal diseases such as osteogenesis imperfecta [39] and congenital disorders such as metachromatic leukodystrophy [40].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the i.v. infusion of allogeneic MSC in humans has led to encouraging results in different human diseases including GVHD [15], breast cancer [71], osteogenesis imperfecta [72], metachromatic leukodystrophy and Hurler syndrome [73], hematological malignancies [74] and stroke [75]. However, recent in vivo experiments raised some doubts about the reported immunoprivilege of MSC, indicating that at least in some cases, administration of allogeneic MSC into an MHC-mismatched host may result in their rejection [19].…”
Section: Msc-mediated Immunological Effects In Vivomentioning
confidence: 99%